Contents and efficiency measures of psychoeducation in rehabilitation system of patients with bipolar affective disorder - Rezunenko, Oleg; Kozhyna, Hanna; Markova, Marianna (Journal of Education, Health and Sport, 2017)
The objective: to formulate, test and endorse psychoeducational activities in the system of bipolar affective disorder (BAD) patients rehabilitation. 158 BAD patients had complex clinical-psychopathological, clinical anamnesis and psychodiagnostic examination. Developed algorithm of psychoeducational measures involves the use of various information modules, techniques, cognitive-behavioural therapy, training interactions (positive self-image, improved compliance, formation of communication skills, problem solving, interpersonal interaction), problem-oriented discussions and family therapy. The high efficacy of psychoeducation compared to traditional treatment complex ( activation of adaptive coping strategies, transition type of maladaptive relationship to disease in adaptive, positive dynamics of social and quality of life of patients with BAD) has been ascertained.